Blood–brain barrier dysfunction following traumatic brain injury: correlation of Ktrans (DCE-MRI) and SUVR (99mTc-DTPA SPECT) but not serum S100B. (2nd June 2015) - Winter, Craig; Bell, Christopher; Whyte, Timothy; Cardinal, John; Macfarlane, David; Rose, Stephen
Abstract : Objective: Damage to the blood–brain barrier (BBB) is an important secondary mechanism that occurs following traumatic brain injury (TBI) and may provide a potential therapeutic target to improve patient outcome. For such a progress to be realised, an accurate assessment of BBB compromise needs to be established. Methods: Fourteen patients with TBI were prospectively recruited. Post-traumatic BBB dysfunction was assessed using dynamic contrast-enhanced MRI (DCE-MRI), single-photon emission computerised tomography (SPECT) and serum S100B levels. Results: A statistically significant correlation between standardised uptake value ratio (SUVR) calculated from 99mTc-DTPA SPECT and K trans (a volume transfer constant) from DCE-MRI was found for those eight patients who had concurrent scans. The positive correlation persisted when the data were corrected for patient age, number of days following trauma and both parameters combined. We found no statistically significant correlation between either of the imaging modalities and concurrent serum S100B levels. Discussion: The correlation of SPECT with DCE-MRI suggests that either scan may be used to assess post-traumatic BBB damage. We could not support serum S100B to be an accurate measure of BBB damage when sampled a number of days following injury but the small number of patients, the heterogeneity in TBI patients and the delay following injury makes any firm conclusions regarding S100B and BBB difficult.